Antibacterial efficacy of silver nanoparticles and ethyl acetate's metabolites of the potent halophilic (marine) bacterium, Bacillus cereus A30 on multidrug resistant bacteria. (3rd October 2017) - Arul, Dhayalan; Balasubramani, Govindasamy; Balasubramanian, Velramar; Natarajan, Thillainathan; Perumal, Pachiappan
Abstract: Bacteria are generally responsible for the prevalence of several diseases and pathogenic bacteria are showing increasing resistance to different antibacterials. During the present study an extremophilic bacterium-A30 isolated from the marine waters was characterized and evaluated against four multi-drug resistant (MDR) pathogens, viz ; Methicillin-resistant Staphylococcus aureus (MRSA), Escherichia coli, Klebsiella pneumoniae, and Pseudomonas aeruginosa . The sensitivity pattern of the selected pathogens was tested with 31 antibiotics. Among the 47 marine microbial extracts tested on 4-MDR pathogens viz : Methicillin-resistant Staphylococcus aureus (MRSA), E. coli, K. pneumoniae and P. aeruginosa, only our strain A30 strain exhibited highest efficacy. This strain was subsequently subjected to 16S rDNA sequencing which confirmed its allocation as Bacillus cereus . Silver nanoparticle (AgNPs) synthesis and ethyl acetate extraction were performed using the supernatant of B. cereus . The synthesized AgNPs were characterized by UV-Visible, Fourier-transform infra-red (FT-IR), X-ray diffraction (XRD), Field emission-scanning electron microscopy (FE-SEM), energy dispersive X-ray spectroscopy (EDX), and Zeta potential analyses. The presence of functional groups and 13 bioactive components in the ethyl acetate extract were analyzed using FT-IR and gas chromatography-mass spectrometry (GC-MS). The synthesized of AgNPs and the ethyl acetate extract showed preponderant activity against P. aeruginosa and MRSA, respectively. The effects of AgNPs were significant when compared to ethyl acetate extract. Therefore, the halophilic bacterium, B. cereus mediated AgNPs could provide antibacterial applications in the biomedical industries.